Multi-tiered bio-inspired self-healing architectural paradigm for software systems - Azween Abdullah,; Ria Candrawati,; M.Agni Catur Bhakti, (Penerbit UKM, 2009)
Self-healing capabilities have begun to emerge as an interesting and potentially valuable property of software systems. Self-healing characteristic enables software systems to continuously and dynamically monitor, diagnose, and adapt themselves after a failure has occurred in their components. However, developing such a software system is a significant challenge. Nature introduces to us exceptional concepts in terms of presenting biological systems that have the ability to handle its abnormal conditions. Based on this observation, this work presents a self-healing architecture for software system based on one of the biological processes that have the ability to heal by itself- the wound-healing process. The self-healing architecture provides software systems with the ability to handle anomalous conditions that appear among the components. The presented architecture is divided into two layers, functional layer and healing layer. To demonstrate the functionality of the proposed self-healing software system, a formal description of the architecture is presented.